Moderation Effect Of Debt Policy On Factors Affecting Company Value In The Jakarta Islamic Index - Puji Purwani; Endah Nur Fitriyani (LPPM ISNJ Bengkalis, 2023)
This study analyzes the factors that affect the company's value, moderated by the debt policy. The population in this research is 49 companies listed on the Jakarta Islamic Index (JII). Determination of the sample using purposive sampling method to obtain 15 companies. The data analysis technique used moderated regression analysis (MRA). The study's results partially found that dividend policy and institutional ownership do not affect firm value. Company growth positively and significantly affects firm value. Debt policy negatively and significantly affects firm value. Debt policy cannot moderate the effect of dividend policy and company growth on firm value. However, debt policy can moderate the effect of institutional ownership on firm value. Research can complement existing theories and become a reference for company management in advancing companies and investors in investing capital.